Pemanfaatan Augmented Reality (AR) sebagai Media Pembelajaran Kelas VII SMPN 1 Rambah - Bella Salsabila; Ahmad Akhyar; Agung Setiawan; Detri Amelia Chandra (Departement of Mathematics Education, 2023)
The development of information technology by the International Telecommunication Union (ITU), Indonesia is ranked 108 out of 167 countries in the world in the ICT Development Index (IDI). Learning media is needed as an intermediary for conveying messages, in order to minimize failures during the communication process. The selection of learning media must be attractive to students so that it is not boring. Augmented Reality (AR) must be implemented in schools, because the use of Augmented Reality (AR) as a learning medium can further enhance student enthusiasm for learning with its advantages. Research uses research and development (research and development) by utilizing Augmented Reality (AR) technology. The product developed is Augmented Reality (AR) technology-based learning media for social studies subject matter on geographical location with sample data of 10 class VII students of SMPN 1 Rambah. The research objective is to find out the increase in Augmented Reality (AR) learning media in improving the quality of learning. The class teacher's assessment includes aspects of the quality of media display, software engineering, presentation of material, use of language, evaluation, implementation, and curriculum. Overall an average score of 4.23 or 84.6% is categorized as good (B). Student responses regarding the implementation of the use of AR in every aspect, namely interest in learning, ease of understanding, display, and implementation. The highest results were obtained on the aspect of interest in learning, namely 94% in the very good category (SB), so it can be concluded that AR is very helpful in increasing student interest in learning.